ORGANIZATIONAL CULTURE OF RUSSIAN UNIVERSITIES: EXPECTATIONS AND REALITIES - O. B. TOMILIN; I. M. FADEEVA; O. O. TOMILIN; A. K. KLUYEV (Высшее образование в России, 2018)
The article analyzes changes in the profile of organizational culture of an average Russian university during the last 13 years (2003–2016), diagnosed with the use of OCAI methods. The research base of the article consists of poll results obtained by the authors in 2003–2005 and 2016. It is shown that during that period of time Russian higher education demonstrated significant deviation of university organizational culture from its planned state. Modernization processes in higher education caused universities to form adaptation reactions different from those designed at the stage of designing new development institutions. Research data allow identifying a gap between expectations concerning modernization of university organizational couture and real trends, including the growth of bureaucratic component and decrease of real autonomy and independence of academic staff, increased imbalance in corporate values of university communities creating new risks and threats for higher education development. The influence of such factors as university type, respondent’s position, profile of subjects taught on the cultural mindset of university staff was also defined. The novelty of the research is in the analysis of change dynamics in university organizational culture, defining more complicated mechanisms of its transformation and development that do not allow implementing simple linear solutions for forming modern university culture.